(3HQfGeL GHf CHj GdQHjYs - (3GdbGSe Hf YHO Gddg Hf eMeO Hf GdTGW GdCfUGQj GdSHJj, GHf GdTGW , SQGL GdOjf,J (B723 (3g` s ((3YHO Gddg Hf jhSa GdeQLGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe YdjfG HgOGjJg s
(3BNQgG (B:s
(3bGd Pdc MGeOkG ddg JYGdi heUdjkG Ydi SjOfG eMeO hYdi Bdg hUMHg heSdekG JSdjekG cKjQkG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs